An enhanced model for an extreme wave impacting a vertical cylinder - Tai, B; Ma, Y; Dong, G; Koh, CG; Tang, T; Perlin, M (Elsevier, 2024)
The interaction between extreme waves and a vertical cylinder is a complex process due to the intricate impact physics, three-dimensional effects, and unique characteristics of breaking waves. To improve wave force predictions, an enhanced model based on a finite-water-extent slamming theory that incorporates wave profiles is proposed. In contrast to the infinite-water-extent assumption in typical wave slamming theories, a finite volume of water with dual free surfaces is used, which better captures the wave's boundary conditions. Strip theory and potential flow theory are adopted to calculate sectional wave forces on the cylinder by solving the governing and boundary equations. The wave profiles, which provide the boundary conditions, result in a more realistic distribution of sectional forces than the often-assumed uniform distribution. Comparison with experimental data shows that the proposed model indeed provides more accurate wave force predictions and exhibits a gradual rise in impact force instead of an abrupt change observed in commonly used models.